2012
DOI: 10.1007/s00701-012-1361-x
|View full text |Cite
|
Sign up to set email alerts
|

The denticulate ligament: anatomical properties, functional and clinical significance

Abstract: DL histology and anatomy are strongly correlated with the function of this structure at different spinal levels. It is important to have accurate knowledge about DLs as these structures are relevant for clinical procedures that involve the spinal cord or craniovertebral junction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(19 citation statements)
references
References 13 publications
0
18
0
1
Order By: Relevance
“…Similarly, a midline dorsal septum is present. Each of these three structures merges with the inner aspect of the dura mater and helps anchor the cord (7,8).…”
Section: Teaching Pointsmentioning
confidence: 99%
“…Similarly, a midline dorsal septum is present. Each of these three structures merges with the inner aspect of the dura mater and helps anchor the cord (7,8).…”
Section: Teaching Pointsmentioning
confidence: 99%
“…Anatomy textbooks mention that the last DL is located at the T12-L1 level (Hollinshead, 1982;Williams and Newell, 2005). Also, Ceylan et al (2012) reported that no DL was found at the lumbar segment in their study. In our study, the most caudal DL was found to be located in the L1-2 level (31.2%) or most commonly in the T12-L1 level (68.8%).…”
Section: Discussionmentioning
confidence: 75%
“…Previous studies as well as anatomical textbooks mentioned that all DLs were triangular in shape (Teng, ; Epstein, ; Nicholas and Weller, ; McCormick and Stein, ; Williams and Newell, ; Ceylan et al, ). In contrary, our study shows that in the cervical segment all DLs were triangular in shape; but as soon as thoracic segment begins DLs changed their shape to “Y.”…”
Section: Discussionmentioning
confidence: 99%
“…Auch ein Septum medianum dorsale ist vorhanden. Alle diese 3 Strukturen verschmelzen mit dem inneren Aspekt der Dura mater und dienen der Aufhängung des Rückenmarks [7,8].…”
Section: Arachnoidea Mater Und Pia Materunclassified